Drought and heat stress effects on gluten protein composition and its relation to bread-making quality in wheat. (November 2022) - Olckers, Schae-Lee; Osthoff, Garry; Guzmán, Carlos; Wentzel, Barend; van Biljon, Angeline; Labuschagne, Maryke
Abstract: Wheat grain proteins are largely affected by environmental conditions, with drought and heat stress causing considerable changes to gluten composition, resulting in variations in bread-making quality. Size-exclusion high-performance liquid chromatography (SE-HPLC) was used to assess the effects of moderate and severe drought and heat stress on variation in gluten proteins in bread wheat cultivars. Extractable gliadin (exGLi), mixing time (MixT) and total polymeric proteins (TPP) were largely genetically determined, while flour protein content (FPC) and extractable albumins/globulins (exAG) were significantly affected by treatment. The two levels of both heat and drought stress caused differential expression of gluten proteins. The unextractable polymeric proteins were reduced under severe heat stress, while both extractable and unextractable low molecular weight glutenin fractions were increased, leading to a weakening of the dough and deterioration of quality. Severe drought caused increased values of all bread-making related characteristics and loaf volume (LV), coupled with significant increases in unextractable polymeric and monomeric proteins and exGLi. Moderate heat stress caused increases in extractable HMW glutenin, which negatively affected bread-making characteristics. The large and total polymeric proteins were consistently correlated with LV for all treatments, although extractable HMW glutenins were generally negatively correlated with baking characteristics under all treatments. Graphical abstract: Image 1 Highlights: Two heat/drought stress intensities caused differential gluten protein expression. Unextractable polymeric proteins reduced under severe heat. Severe drought caused an increase in unextractable polymeric proteins. Moderate heat stress caused increases in extractable HMW glutenin. Large and total polymeric proteins consistently related with LV for all treatments.